Hydroxyquinolines Inhibit Ribonucleic Acid-Dependent Deoxyribonucleic Acid Polymerase and Inactivate Rous Sarcoma Virus and Herpes Simplex Virus - Rohde, Wolfgang (1976)
8-Hydroxyquinoline and several of its derivatives inactivate the transforming ability of Rous sarcoma virus and inhibit its ribonucleic acid-dependent deoxyribonucleic acid polymerase activity. The copper complex of these metal-binding ligands is as active as the free ligand. The activity of the 8-hydroxyquinolines is approximately 50-fold more effective than another group of metal-binding compounds that we have tested, the thiosemicarbazones. In contrast to the potency of the 8-hydroxyquinolines to inactivate Rous sarcoma virus, no intracellular inhibition of transformation could be demonstrated at a concentration that did not affect the growth and appearance of the cells. Cellular deoxyribonucleic acid synthesis was inhibited to a greater extent than was ribonucleic acid or protein synthesis. The phenomenon of “concentration quenching” was observed with high concentrations of drug, causing less inhibition of deoxyribonucleic acid synthesis than was observed with lower concentrations. Herpes simplex virus type 1 was inactivated also by the 8-hydroxyquinolines and their copper complexes. No intracellular inhibition of plaque formation was observed. Treatment with 8-hydroxyquinoline sulfate had no effect on the resolution of herpetic keratitis in rabbits. Some 8-hydroxyquinolines bind to deoxyribonucleic acid in the presence of copper, a phenomenon that may be important in their antiviral activity.